Group search optimization for combined heat and power economic dispatch. (June 2016) - Basu, M.
Highlights: This paper presents GSO to solve non-smooth non-convex CHPED problem. Valve-point loading and prohibited operating zones are taken into account. The effectiveness of the proposed method has been verified on four test systems. Abstract: This paper presents group search optimization to solve the complex non-smooth non-convex combined heat and power economic dispatch (CHPED) problem. Valve-point loading and prohibited operating zones of conventional thermal generators are taken into account. The effectiveness of the proposed method has been verified on four test systems. The results of the proposed approach have been compared with those obtained by other evolutionary methods. It is found that the proposed group search optimization based approach is able to provide better solution.